COPYRIGHT EDUCATION PROGRAMS IN ACADEMIC INSTITUTIONS (NATIONAL CAPITAL LAW JOURNAL, 2008)
NA
Keywords: Copyright Education; Academic Institutions; Copyright Policy; Fair Use; Intellectual Property Rights; Copyright Literacy; Plagiarism; Software Piracy; Copyright Infringement; Information Literacy; Online Education; Copyright Management; Cyber Ethics; Copyright Awareness.